Endovascular Treatment in Acute Ischemic Stroke: From Randomized Studies to Current Treatments - Asil, Talip; Gürkaş, Erdem; Giray, Semih; Aslan, Abdullah Taha; Eren, Alper; Ozkul, Ayca; Ozdemir, Atilla Ozcan (My University, 2025)
Rapid advances have been made in the treatment of acute ischemic stroke over the last 3 decades. Endovascular treatments have become the gold standard treatment in patients with large vessel occlusion, especially in the presence of penumbra, but due to the nature of ischemic stroke, it has become necessary to make treatment decisions in many controversial patient groups such as patients with distal occlusions and lpatients with arge core infarct. It is aimed to achieve good clinical results in more patients through national and international guidelines created all over the world. In this review written about the endovascular treatment of acute ischemic stroke, where there have been very rapid developments in recent years, large studies, meta-analyses and recommendations in international guidelines on this subject are summarized and recommendations are tried to be made for our country.
Keywords: Acute ischemic stroke; endovascular treatment; mechanical trombectomy